The Dynamics of Savings Mobilisation in Lesotho - Simelane, Bongile; Odhiambo, Nicholas M. (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2019)
This paper provides a conceptual analysis of the dynamics of savings in Lesotho for the period 1960 to 2017. The study is motivated by the low and sometimes negative savings rate and the declining level of economic growth prevailing in Lesotho during the period from 1960 to 2017.The study analyses the behaviour of savings in Lesotho, using the savings trends for the country ever since it obtained independence in 1966.The study further examines the policies that the government of Lesotho has implemented in order to promote savings in the country. The government adopted a policy on rural savings and credit schemes as a means of promoting savings in Lesotho. The purpose of the policy is to improve access to credit for the rural population. The study has identified some challenges that impede savings mobilization in Lesotho. The major savings challenge in Lesotho is the lack of banking facilities in rural areas.